A cross sectional study on severe acute maternal morbidity near-miss at tertiary care centre in Hyderabad, Telangana, India - Mummadi, Mahesh Kumar; Javvaji, Sowmya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: A maternal near-miss case is defined by World Health Organization (WHO) as “a woman who nearly died but survived a complication that occurred during pregnancy, childbirth or within 42 days of termination of pregnancy.” Severe acute maternal morbidity (SAMM) is the acronym for the more popular term of ‘near-miss’ cases. There are approximately 118 life threatening events of “near miss mortality” or SAMM for each maternal death. Analysing near miss cases can prevent maternal death. Methods: It is a retrospective study based on medical records. Sample size is all the pregnant cases admitted in Department of Obstetrics and Gynecology in AIMSR, Hyderabad, Telangana, India over the period of January 2015- June 2017 (two and half years) i.e. 2276. All records were gathered and each record that satisfy near miss criteria/maternal mortality were segregated, data has been collected on the occurrence of severe pregnancy-related complications or those who require critical interventions and admission to intensive care unit as per the proforma (according to WHO near miss questionnaire). Data entry done in MS Excel and analyzed using Epi Info. Results: Total MNM/SAMM patients were 85 out of 2276 pregnant women (3.7%). The duration of the stay, potential life-threatening conditions (PTLC), critical interventions, organ dysfunctions, mode of delivery, treatment for PPH, hypertensive disorders and associated conditions among SAMM patients were calculated. SAMM patients who has severe post-partum hemorrhage PPH were 24.7%, severe pre-eclampsia was 31.7%, eclampsia was 2.4%, patients with both severe PPH and eclampsia were 2.4%. Conclusions: Near misses can be prevented to some extent by spreading awareness about possible obstetric complications and risk stratification. The WHO tool for analysis of maternal near miss or SAMM can identify more preventable causes of maternal death. Prospective monitoring of maternal morbidity may be useful in identifying determinants of severe maternal mortality.